2015
DOI: 10.5145/acm.2015.18.3.94
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Fungemia Caused byCyberlindnera fabianiiwith Anidulafungin: A Case Report

Abstract: Cyberlindnera fabianii (previously known as Hansenula fabianii, Pichia fabianii, and Lindnera fabianii) is a yeast species that forms a biofilm, allowing it to resist azole drugs. In this study, we report a case of fungemia with C. fabianii that was successfully treated with anidulafungin. In this case, the organism was initially misidentified as Candida utilis (with a high probability of 93%, suggesting good identification) using the VITEK 2 yeast identification card (YST ID; bioMérieux, USA). The species res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In South Korea, there have been three case reports of Cy. fabianii from bloodstream [4,6,7]. In a recent survey of Czech hospitals, Cy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In South Korea, there have been three case reports of Cy. fabianii from bloodstream [4,6,7]. In a recent survey of Czech hospitals, Cy.…”
Section: Discussionmentioning
confidence: 99%
“…Until now in Korea, Cy. fabianii isolates originated only from bloodstream and antifungal susceptibility testing was conducted on one isolate using anidulafungin [6]. Thus, it is the first report to perform in vitro antifungal susceptibility test using nine antifungal agents in order to select appropriate and effective antifungal therapy and supervise the development of resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these emerging Candida spp., C. fabianii (anamorph Candida fabianii) is one such species, which exhibits reduced susceptibility to fluconazole, itraconazole and posaconazole . Until September 2017, 21 patients with C. fabianii infection (including 14 patients with fungaemia) have been reported from different countries across Asia (n = 6), Europe (n = 12) and America (n = 3) (Table ) . Similar to our study, nearly half of these cases also occurred in paediatric age group, mostly including neonates (n = 7).…”
Section: Discussionmentioning
confidence: 99%
“…All the patients responded favourably with cultures becoming negative between 15 and 40 days following therapy . Echinocandins have also recently been used for the treatment of C. fabianii infection in some patients, and the therapeutic response has been generally good (Table ) . In this regard, Lee et al reported an interesting case of C. fabianii fungaemia in an 87‐year‐old man with lung cancer .…”
Section: Discussionmentioning
confidence: 99%